Penggunaan Obat Herbal untuk Meningkatkan Libido Mencit Jantan (Mus musculus): Tribulus terrestris dan Panax ginseng - Kirtishanti, Aguslina; Wulansari, Devyani Diah; Kesuma, Dini; Dwi Putri, I Gusti Ayu Laksmi; Rahmadinar, Amirah Nabila (Faculty of Pharmacy, Universitas Pancasila, 2023)
Tribulus terrestris and Panax ginseng are two therapeutic plants that might increase libido. The aim of the study was to see the effects of herbal medicine containing Tribulus terrestris and Panax ginseng on increasing male mice libido. This study used mice divided into two sets of 7 and 14 days. Each group was divided into four parts: control (solvent), comparator (Vitan), and test 1 (herbal medicine). Parameters measured were mice sexual behaviour (introduction, climbing, coitus), sperm concentration, sperm motility, and testicular weight. Except for coitus behaviour, there were no significant changes between groups in the 7 days of treatment. There were significant differences in introduction and climbing behaviour between the control group and test 2 after 14 days of treatment, but not in other parameters. There were no significant variations in any parameters of the mice’s libido between 7 and 14 days of treatment with 1x dose of herbal medicine; however, with 2x doses, only introduction behaviour showed a significant difference. Based on the research results, it can be concluded that administering two doses of herbal medicine can increase the frequency of treatment for 14 days.